Traditional and minimally invasive access cavities in endodontics: a literature review - Ioanna Kapetanaki; Fotis Dimopoulos; Christos Gogos (Restorative Dentistry & Endodontics)
The aim of this review was to evaluate the effects of different access cavity designs on endodontic treatment and tooth prognosis. Two independent reviewers conducted an unrestricted search of the relevant literature contained in the following electronic databases: PubMed, Science Direct, Scopus, Web of Science, and OpenGrey. The electronic search was supplemented by a manual search during the same time period. The reference lists of the articles that advanced to second-round screening were hand-searched to identify additional potential articles. Experts were also contacted in an effort to learn about possible unpublished or ongoing studies. The benefits of minimally invasive access (MIA) cavities are not yet fully supported by research data. There is no evidence that this approach can replace the traditional approach of straight-line access cavities. Guided endodontics is a new method for teeth with pulp canal calcification and apical infection, but there have been no cost-benefit investigations or time studies to verify these personal opinions. Although the purpose of MIA cavities is to reflect clinicians' interest in retaining a greater amount of the dental substance, traditional cavities are the safer method for effective instrument operation and the prevention of iatrogenic complications.